Clinical pairing revisited: a study at the University of Malaya, Malaysia - Ahmad , Norasmatul Akma; Naimie, Zahra; Lui, Joo Loon; Abdul Aziz, Azwatee; Abdullah, Mariam; Abu Kasim, Noor Hayati; Abu Kassim , Noor Lide; Chooi, Gait Toh; Yo, L. Thong; Abdul Razak, Abdul Aziz; Abdullah , Hadijah; Che' Abdul Aziz, Zeti Adura; et al. (Education American Dental Education Association, 2012)
This study is part of ongoing educational research conducted by the Department of Conservative Dentistry, University of Malaya, Malaysia, to evaluate the perception of clinical pairing. A thirteen-question survey was distributed to 148 dental students after they had experienced four-handed dentistry. The objectives were to identify the advantages, disadvantages, and the acceptance of the implementation of clinical pairing from the students' point of view. The responses from the open-ended questions were categorized into six main themes (areas of interest): quality-related (Q), patient-related (PT), partner-related (P), lecturer-related (T), infection control (IC), and learning environment (L). Data analysis was done using SPSS version 18. Results indicated that the students perceived they possessed enough knowledge regarding clinical pairing. However, it was found that they still preferred to work independently as compared to working in pairs. The benefits of clinical pairing may not be viewed in the same vein by both dental students and teachers. The quality-related theme was perceived by students as the main advantage of clinical pairing, whilst the partner-related theme was perceived otherwise. The study also revealed that students may have some preconceived notions about pairing that may have impaired their acceptance. As a consequence, some reluctance was seen in their responses.